The Nitrone Spin Trap 5,5-Dimethyl-1-pyrroline N-oxide Affects Stress Response and Fate of Lipopolysaccharide-Primed RAW 264.7 Macrophage Cells - Zhai, Zili (2013)
The nitrone spin trap 5,5-dimethyl-1-pyrroline N-oxide (DMPO) is commonly used to study free radicals. Due to its free radical trapping properties, DMPO is thought to reduce free radial-mediated oxidative damage and other related cellular responses. The purpose of this study was to assess the effect of DMPO on lipopolysaccharide (LPS)-induced inflammation, endoplasmic reticulum (ER) stress, and apoptosis in RAW 264.7 cells. The results showed that DMPO at 50 mM inhibited inducible nitric oxide synthase expression when added shortly after LPS treatment (≤3 h). Interestingly, DMPO increased anti-inflammatory heme oxygenase-1 (HO-1) expression and reversed LPS-induced decrease in HO-1 expression. LPS could increase cellular ER stress as indicated by C/EBP homologous protein (CHOP) induction; DMPO reduced LPS effect on CHOP expression. Unexpectedly, DMPO had a synergistic effect with LPS on increased caspase-3 activity. Overall, DMPO harbors multiple modulating effects but may induce apoptosis in LPS-stressed cells when given at 50 mM, an effective dose for its anti-inflammatory activity in vitro. Our data provide clues for further understanding of the nitrone spin trap with therapeutic potential.